RELEVANT ASPECTS REGARDING THE EUROPEAN UNION INDEPENDENCE ON ENERGY IMPORTS - ANGHEL MĂDĂLINA-GABRIELA; IACOB ȘTEFAN VIRGIL; STRIJEK DENIS-ARTHUR (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie)
Following the outbreak of the armed conflict between Russia and Ukraine, in order to limit the European Union's dependence on Russian gas, the EU initiated the RepowerEU Plan, with the aim of saving energy, diversifying energy supply and accelerating the transition to green energy, by increasing investments in renewable sources. In this paper, we aimed to identify whether the EU's independence from natural gas imports was ensured through the measures implemented at the level of the European Union. In order to achieve the purpose of the research, we analyzed the evolution of some indicators that characterize the energy sector in the European Union and in the member states, such as the total degree of energy dependence, as well as the dependence on energy imports by product category: oil and petroleum products, natural gas or solid fossil fuels. In this sense, we used the data published by Eurostat, in the period 2010-2023. In order to highlight the data more clearly, we used the statistical tools, by representing them graphically and in tabular form. In order to make a comparative analysis of the evolution / performances of energy systems in various countries, we applied the model based on time series analysis. These analyzes allow the exact position of a certain national energy system in relation to similar energy systems. We had in mind that, based on the calculated indicators, we would make comparisons in time and space. Following the study we can conclude that, although natural gas imports from Russia decreased from 45% in 2021 to 15% in 2023, as a result of the measures adopted at the EU level, the dependence on imports from Russia was only changed to dependence on imports from other countries, playing a role with Norway. Thus, the EU's dependence on individual countries is maintained.